Towards better integration of environment and ecosystem health in the One Health concept - (:unkn) unknown (My University, 2024)
Source Agritrop Cirad (https://agritrop.cirad.fr/611655/) * Autres projets (id;sigle;titre): FED/2021/428-198;COHESA;(EU) Capacitating One Health in Eastern and Southern Africa//
Keywords: African Research